Using multi-objective evolutionary algorithms in the optimization of polymer injection molding - Fernandes, Célio Bruno Pinto (2009)
A Multi-objective optimization methodology has been applied in the optimization of polymer injection molding process. This allowed the optimization of the operating conditions of the process from mold flow simulations, taking into consideration the existence of 5 criteria simultaneously, such as temperature dif-ference on the molding at the end of filling, the maximum pressure, the pressure work, the volumetric shrinkage and the cycle time. The results produced shown that the proposed methodology is an efficient tool to be used in the optimization of this process.